Implementation of Verilog HDL in Calculator Design with FPGA Simulation - Shamsiah, Suhaili; Kayle Jacqueline, Kumar; Norhuzaimin, Julai; Maimun, Huja Husin; Mohd Faizrizwan, Mohd Sabri; Asrani, Lit (IEEE, 2020)
A calculator is a device that can be found in daily life. This paper proposed the design of a calculator using Verilog HDL. A series of synthesizable Verilog code was created and simulated on Quartus II 15.0. The design of an 8-bit calculator can solve mathematical operations such as addition, subtraction, multiplication, division, square and cube functions, square root and factorial. This calculator consists of eight-digit numbers. In this paper, among the family devices in Altera, Cyclone V was used to perform the simulation process. The outputs are shown in the RTL viewer and waveform simulation of the calculator design. The implementation of a calculator was successfully designed using Verilog HDL in terms of digit numbers and the operation of the calculator function.